2020
DOI: 10.1111/maps.13585
|View full text |Cite
|
Sign up to set email alerts
|

Biconical reflectance, micro‐Raman, and nano‐FTIR spectroscopy of the Didim (H3‐5) meteorite: Chemical content and molecular variations

Abstract: The Didim meteorite contains multiple lithologies and clasts of different petrologic types in a single stone. A mixture of H5 clasts in an unequilibrated H3 host was previously observed in Didim, according to the initial characterization reported in the Meteoritical Bulletin Database, providing an opportunity to investigate molecular composition that contains varying degree of equilibrium with varying mineralogy. We have taken a "from large scale to small scale" approach to spectroscopically investigate the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 56 publications
(127 reference statements)
3
17
0
Order By: Relevance
“…Figure 10 shows a comparison of the amplitude and phase spectra of positions A, D, and B, as well as nano‐FTIR amplitude and phase spectra of single crystal enstatite (this study), forsterite (Dominguez et al., 2014), and olivine chondrule spectra from Yesiltas et al. (2020). The phase spectra of points A and D have prominent features around 925, 960, and 985 cm −1 , suggesting that the material these spectra represent are compositionally similar.…”
Section: Discussionmentioning
confidence: 94%
“…Figure 10 shows a comparison of the amplitude and phase spectra of positions A, D, and B, as well as nano‐FTIR amplitude and phase spectra of single crystal enstatite (this study), forsterite (Dominguez et al., 2014), and olivine chondrule spectra from Yesiltas et al. (2020). The phase spectra of points A and D have prominent features around 925, 960, and 985 cm −1 , suggesting that the material these spectra represent are compositionally similar.…”
Section: Discussionmentioning
confidence: 94%
“…The mineralogies of a carbonaceous chondrite and a cometary dust grain have been investigated at ~ 20 nm spatial resolution using nano-FTIR, although within a limited (1100–800 cm −1 ) spectral range 33 . Recently, molecular variations at the ~ 20 nm spatial scale were shown for meteoritic minerals within 1600–850 cm −1 34 . Kebukawa et al 35 reported nano-FTIR analyses of organics and minerals in two carbonaceous chondrites with ~ 30 nm spatial resolution using photothermal nano-FTIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Dark clasts are present in many different types of meteorites including chondrites and achondrites. Dark clasts are usually carbon- and organic-rich and are often foreign to the host meteorite (i.e., xenolithic clasts in ordinary chondrites ,, and howardites. , On the contrary, the organic matter in CM chondrites is usually present in their matrices and that the dark clasts in CM chondrites may host more carbon, thus organic matter, compared to the matrix.…”
Section: Introductionmentioning
confidence: 99%